The geology, mineralogy, structure and economic aspects of the pegmatite-hosted Swanson Tantalum Deposit, Tantalite Valley area, southern Namibia - Pepler, Laubser (Rhodes University, Faculty of Science, Department of Geology)
This study presents the geology, mineralogy, structure, and economic aspects of the recently explored Swanson Tantalum Deposit occurring within the Namaqua Sector of the Namaqua Natal Metamorphic Province, Tantalite Valley area, southern Namibia. It is an LCT-type pegmatite hosted (microlitetantalite- tapiolite Â± spodumene "“ lepidolite - zinnwaldite) tantalum deposit forming part of a highly localised sill-and-dyke swarm comprised of 15 shallow dipping and significantly mineralised pegmatites. This deposit forms part of the western portions of the regionally developedâˆ¼ 1040 "“ 950 Ma Orange River Pegmatite Belt (ORPB) which was locally emplaced syn-tectonically into competent host rocks in the core zone of the late-stage crustal scale transcurrent dextral, ductile to brittle-ductile D4 Marshall Rocks "“ Pofadder Shear Zone (MRPSZ), where it crosscuts the rocks of the D2 Lower Fish River - Onseepkans Thrust Zone (LFROTZ). A JORC Maiden Mineral Resource of 1.2 Mt @ 412 ppm Ta2O5 + 76 ppm Nb2O5 + 0.29 wt. % Li2O (with an applied cut-off grade of 236 ppm Ta2O5 and a minimum thickness of 1 m) has recently been estimated for the deposit. The deposit is currently being advanced to feasibility stage with the aim of outlining economic Mineral Reserves. It currently hosts a globally significant and market-relevant "high grade "“ low tonnage" tantalum Mineral Resource. Recent litho-structural mapping of this deposit has shown that its structural setting encompasses a locally developed lower strain extensional quadrant associated with the mega-scale shear zone bound competent mantle porphyroclast: the mafic-ultramafic Tantalite Valley Complex (TVC), or TVC megaclast. A succession of syn-D4 MRPSZ-hosted granitic melts comprising earlier leucogranite intrusions and later mineralised pegmatites of the Swanson Tantalum Deposit have variably utilised this extensional structure. The earlier leucogranites have clearly exploited mylonitic foliations associated with the development of core zone of the MRPSZ, while the mineralised pegmatites have utilised later-stage shallow-dipping Riedel fractures developed within more competent host rock. The tantalum tenor of pegmatites comprising the Swanson Tantalum Deposit is clearly structurally controlled, with tantalum tenor increasing from NW towards the SE over relatively short distances, toward the TVC megaclast. Although highly speculative without robust geochronological and petrographic investigation, field observations from this study highlights that the host rocks to the Swanson Tantalum Deposit, namely the mottled hybrid metagabbro (HMG), usually described as being syn-D2 in age (âˆ¼ 1200 "“ 1100 Ma), may possibly be syn-D4 in age (âˆ¼ 1040 "“ 950 Ma). If this is proven to be true, it may represent the earliest syn-D4 melt known for the MRPSZ. The Swanson Tantalum Deposit area therefore represents a prime area for studying and potentially constraining the upper and lower age limits of the MRPSZ.
Keywords: Pegmatites -- South Africa Pofadder (Region); Tantalum -- South Africa Pofadder (Region); Geology -- South Africa Pofadder (Region); Mineralogy -- South Africa Pofadder (Region); Pegmatites -- South Africa Pofadder (Region) Structure; Pegmatites Economic aspects -- South Africa Pofadder (Region); Pofadder Shear Zone; Tantalite Valley Complex; Orange River Pegmatite Belt; Lower Fish River/Onseepkans Thrust Zone